Unit testing in C++ with compiler instrumentation and friends - Márton, Gábor; Porkoláb, Zoltán (Acta Cybernetica, 2017)
In C++, test code is often interwoven with the unit we want to test. During the test development process we often have to modify the public interface of a class to replace existing dependencies; e.g. a supplementary setter or constructor function is added for dependency injection. In many cases, extra template parameters are used for the same purpose. All existing solutions have serious detrimental effects on the code structure and sometimes on the run-time performance as well. In this paper, we overview existing dependency replacement techniques of C++ and we evaluate their advantages and disadvantages. We introduce our non-intrusive, compiler instrumentation based testing approach that does not have such disadvantages. All non-intrusive testing methods (including our new method) require access to an object’s internal state in order to setup a test. Thus, to complement our new solution, we also present different approaches to conveniently access private members in C++. To evaluate these techniques, we created a proof-of-concept implementation which is publicly available for further testing.